Comprehensive rehabilitation of a patient with Dentinogenesis imperfecta type II: case report - Acosta-de Camargo, María Gabriela; Sánchez, Jesús; Dommar-Gubbins, María Verónica (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Dentinogenesis imperfecta (DI) type II is a rare hereditary dysplasia affecting dentin that occurs during the histodifferentiation stage of tooth development, resulting in dental fractures, especially in the posterior teeth, which often require extraction. This often results in a loss of posterior occlusion and occlusal vertical dimension. In addition to wear and fracture, anterior teeth often have an unaesthetic appearance due to discoloration. Clinical signs also include globular crowns, short roots, and obliteration of root canals. Current treatments of choice are generally suggested to preserve the remaining teeth and tooth structure, allowing for precise and effective treatment with promising potential in the treatment of dentitions affected by DI. This case report describes the comprehensive management of a 30-year-old male patient from his diagnosis, orthodontic, prosthetic-aesthetic treatment, and implant-surgical intervention, demonstrating the restoration of functional occlusion and aesthetics. The results were favorable after a three-year follow-up, contributing to the successful rehabilitation of patients with type II DI. However, well-designed research is needed to conduct long-term follow-ups and obtain evidence-based knowledge.